The Role of Community Social Capital in Building Youth Resilience against Drug Abuse - Nazwa Anzani; Deti Deti; Miftah Jamil Ilhami; Amanda Alicia; Chuol Yuanes Toang (CV. Yazri Aksara Nusantara, 2026)
Drug abuse among adolescents has emerged as a multidimensional social issue amid rapid social transformation and technological advancement. Beyond its detrimental effects on physical and mental health, this phenomenon also threatens the moral and social stability of younger generations. This study aims to examine the role of community social capital in strengthening youth resilience against drug abuse in Pontianak City. The research employed a qualitative case study approach involving youth communities, community leaders, educators, and religious and social institutions actively engaged in drug prevention initiatives. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using thematic analysis techniques. The findings indicate that social capital, reflected in social trust, shared norms, and active community participation, significantly contributes to reinforcing youth resilience. Families, schools, and community environments function as strategic social spaces for fostering moral awareness, collective responsibility, and social solidarity among adolescents. The study concludes that community-based drug prevention strategies grounded in social capital are more sustainable and effective than solely repressive approaches, as they are rooted in local values and social networks embedded within society.Penyalahgunaan narkoba di kalangan remaja telah menjadi persoalan sosial multidimensional di tengah perubahan sosial dan perkembangan teknologi yang berlangsung secara cepat. Fenomena ini tidak hanya berdampak pada kesehatan fisik dan mental, tetapi juga mengancam stabilitas moral dan sosial generasi muda. Penelitian ini bertujuan untuk menganalisis peran modal sosial masyarakat dalam memperkuat ketahanan remaja terhadap penyalahgunaan narkoba di Kota Pontianak. Penelitian menggunakan pendekatan studi kasus kualitatif dengan melibatkan kelompok pemuda, tokoh masyarakat, pendidik, serta lembaga keagamaan dan sosial yang terlibat dalam upaya pencegahan narkoba. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen, kemudian dianalisis menggunakan teknik analisis tematik. Hasil penelitian menunjukkan bahwa modal sosial yang tercermin dalam kepercayaan sosial, norma bersama, dan partisipasi masyarakat berperan penting dalam memperkuat ketahanan remaja. Keluarga, sekolah, dan lingkungan masyarakat menjadi ruang sosial strategis dalam menumbuhkan kesadaran moral, tanggung jawab kolektif, dan solidaritas sosial di kalangan remaja. Penelitian ini menyimpulkan bahwa strategi pencegahan narkoba berbasis masyarakat yang bertumpu pada modal sosial lebih efektif dan berkelanjutan dibandingkan pendekatan represif semata, karena berakar pada nilai-nilai lokal dan jejaring sosial yang hidup di tengah masyarakat.